Exploration and Identification of Endophytic Molds on Leaves and Stem of the Mango’s Mistletoe (Dendrophthoe Pentandra (L.) Miq) - Ayu Pertiwi, Chintya; Abdoes Sjakoer, Nour Athiroh; Jadid Mubarakati, Nurul; Fatimah, Fatimah (Jurnal Riset Biologi dan Aplikasinya, 2023)
Mango’s mistletoe is one of the herbal plants’ rich in bioactivity. Secondary metabolites are not only produced by plants but also by microorganisms that live in tissues. One of these microorganisms is endophytic mold. The ability of endophytic molds to synthesize secondary metabolites is an opportunity for large-scale production in a short time without causing the exploitation of natural materials. This research aimed to explore and identify endophytic molds from the leaves and stem of the mango mistletoe to obtain the genus of molds. The stages of this research consisted of isolation by direct planting with sterilization, purification, growth rate measurement, characterization, and identification carried out macroscopically and microscopically. DBM 1 and DBM 2 belong to Aspergillus sp., DBM 3 belongs to Cladosporium sp., DBM 4 belongs to Neurospora sp., TDBM 1, TDBM 2, and TDBM 3 belong to Hormiscium sp. The growth rate of Aspergillus sp. relatively fast, with the increase in diameter of Aspergillus sp.1 colony from 2.45 cm to 5.05 cm and that of Aspergillus sp.2 from 2.73 cm to 5.35 cm. In the Cladosporium sp., there was an exponential phase with an increase in diameter from 2.15 cm to 4.65 cm. In Neurospora sp., there was an exponential phase with an increase in diameter from 0.63 cm to 3.65 cm. The growth rate of Hormiscium sp. is quite fast, with an exponential phase with an increase in the diameter of the colonies of Hormiscium sp.1 from 2.63 cm to 7.21 cm, Hormiscium sp.2 from 2.45 cm to 6.94 cm and Hormiscium sp.3 from 2.85 cm to 7.85 cm.